Enhancing Learning Effectiveness through the Synergy of Educational Facilities, Infrastructure Management, and Financial Literacy - Akbariansyah Akbariansyah (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2026)
This study examines the synergy between educational facilities, infrastructure management, and financial literacy in enhancing learning effectiveness at SMK PGRI 1 Palembang. Employing a qualitative case study approach, data were obtained through interviews, observations, and document analysis. The findings indicate that effective management practices, including planning, procurement, maintenance, and financial allocation, contribute significantly to improving student engagement, motivation, and practical competencies. Despite challenges related to limited financial resources and coordination, the integration of facilities management and financial literacy plays a critical role in supporting educational quality assurance. The study recommends the implementation of digital asset management systems, strengthened industry partnerships, and increased institutional support to promote sustainable educational development.